Business Computing at Sede del Sur, Universidad de Costa Rica: A Historical overview from 2006 to 2022 - Cruz Alvarado , Mainor (2023)
This article seeks to describe the process that the Business Computing major has undergone at Sede del Sur, Universidad de Costa Rica, since its beginning in 2006, to explain its establishment as a technological major that has given inhabitants from the Brunca Region access to qualified higher education during the period comprised between 2006 and 2022. The teaching activity at Recinto de Golfito, Universidad de Costa Rica, turned into Sede del Sur in 2019, started in 2006. As a matter of fact, it was during this year that the first students enrolled in Business Computing. Ever since then, a total of 88 students, who contribute with the technological growth in the country, have graduated. Data permits to analyze the challenges that determine the need to go deeper into analyzing the learners and their learning processes for the purpose of collecting valuable data that can serve the decision-making stages in regard to the development of the major. To do this, studies to investigate the learners’ sociodemographic situations, as well as the graduated population to evaluate the acquired knowledge and get useful feedback for updating the major.